Pengaruh Harga Komoditas Pertambangan Dunia Terhadap Indeks Saham Syariah Indonesia - Widjiantoro, Surya Tegar (Jurnal Ilmiah Ekonomi Islam, 2023)
This research is using secondary data obtained from trusted global-scale sites. The data is collected from 2015 to 2023 and this research is using monthly time frame. This study uses multiple regression analysis method with 7 (seven) variables, 6 variables X and 1 variable Y. This study was conducted to determine the partial and simultaneous effect of Crude Oil, Silver, Coal, Cobalt, Steel, Nickel variables on ISSI. The results of this study indicate that the variables that have an effect on ISSI are Crude Oil, Silver and Steel variables and the variables that have no effect on ISSI are Coal. Cobalt, Nickel. This is evidenced by the results of the acquisition of each influential variable is Crude Oil (3.204 > 0.677), Silver (-1.146 < -0.677), Steel (2.211 > 0.677), and the variable that has no effect is Coal (0.291 < 0.677), Cobalt (0.259 < 0.677), Nickel (-0.558 > -0.677).